Seismotectonics and Seismic Source Parameters of the Mid-Eastern Iraq - Western Iran Using Moment Tensor Inversion Technique - Mohammed, Hasanain Jasim; Al-Rahim, Ali M. (Iraqi Journal of Science, 2020)
The study area is encompassed by the 33.59-34.93°N latitudes and 45.44-46.39°E longitudes and divided into four groups with respect to earthquake event locations. We determined fault plane solutions, moment magnitudes, focal depths, and trend of slip with the direction of the moment stress axes (P, N, and T) for 102 earthquakes. These earthquakes had a local magnitude in the range between 4.0 and 6.4 for the time period from January 2018 to the end of August 2019, with focal depths ranged between 6 and 17 km. Waveform moment tensor inversion technique was used to analyze the database constructed from seismic stations on local and neighboring country networks (Iraq, Iran, and Turkey). We separated the studied events into four regional subsets (circles). The types of the obtained fault plane solutions are predominantly thrust fault and strike-slip, with the focal depths ranging from 8 to 21 km. A new scaling relation between local magnitude (Ml) and the estimated moment magnitude (Mw) has been developed utilizing a linear regression. Good match results obtained in the present research good match with both seismic trends concluded from earthquake locations and mapped faults. Generally, direction shows NW–SE striking focal planes corresponding with the tectonic framework of the Arabian–Eurasian continental collision zone. The anticlockwise rotation of the Arabian plate that appears accountable for strike-slip displacements on fault surfaces.